Arthroscopic Treatment of Symptomatic Congenital Lunotriquetral Coalition - Apard, Thomas; Mariotte, Benoit; Candelier, Gilles (Journal of Wrist Surgery, 2018)
Symptomatic lunotriquetral coalition is very rare and need open surgery after failure of conservative treatment. We report a case of a symptomatic congenital lunotriquetral coalition type 1 according to the Minaar classification, at the left wrist of a 14-year-old boy. We performed an arthroscopic treatment with two compression screws and without cancellous bone grafting. Healing was obtained at 2 months postoperatively.
Keywords: lunotriquetral; coalition; arthroscopy; surgery; wrist